Analisis minat baca dan motivasi dalam kemampuan membaca pemahaman literal pada teks cerita narasi pada peserta didik kelas V sekolah dasar - Rahmawati, Dita Nur; Rukayah, Rukayah; Ardiansyah, Roy (Universitas Sebelas Maret, 2022)
The aims of this study were to: (1) describe students' reading interest in reading literal comprehension of narrative texts, (2) describe students' learning motivation in reading literal comprehension of narrative texts. The research design used is descriptive qualitative research with a case study approach. The research was carried out at SDN 1 Pantirejo Sragen. The subject of this research was 5th grade students wihich had 13 students. Collecting data using questionnaires, observations, tests, and interviews. The validity of the data used is a triangulation technique with data analysis using the Miles and Huberman interactive model. The results of the research conducted showed that: (1) students' reading interest and motivation in reading comprehension skills were different and not the same, (2) students' reading interest and learning motivation were related to their literal reading comprehension skills.